Occurrence of the Histioteuthis reversa (Verrill 1880), (Cephalopoda/Histioteuthidae) in the Gulf of Mersin/ Turkey - Gökoğlu, Mehmet; Teker, Serkan; Korun, Jale (Universitas Malikussaleh, 2021)
A different species of squid was caught during trawling (36°01390N; 033°44220E and 36°07080N; 034°00920E) in the Gulf of Mersin at average depth of 300-400 m. It was determined that this squid was Histioteuthis reversa (Verrill 1880). This is the first record of Histioteuthis reversa both for the Gulf of Mersin and Turkey's Mediterranean coast.Keywords: Coast of Turkey, Mediterranean, Priacanthus sagittarius, Spread.